Closure - Management, Journal of Infrastructure & Facility Asset (Journal of Infrastructure & Facility Asset Management, 2025)
Journal of Infrastructure & Facility Asset ManagementVolume 7, Issue 1, January 2025                                  (e) ISSN 2656-8896  (P) ISSN 2656-890X Volume 6, Special  Issue 3, January 2024 Effect of Stabilization Soil With Fly Ash and Bottom Ash on Characteristics of Residual Soil (Padang-Sicincin Toll Road) Novema Dwi Saputra, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro & Sri Hastuti HardiningsihEffect of Embankment Construction Pace on Slope Stability Wih Varied Heights on Organic Soft Soil in the Sicincin-Padang Toll Road Sta 10+250-10+400 Alfian Wildan Mulifandi, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro & Sri Hastuti HardiningsihAnalysis Of Behavior And Chemical Stabilization Of Highly Plastic Local Excavated Soil for Embankments In The IKN Highway Project Segment 3A From Karangjoang To KKT Kariangau Mohammad Iqbal Yanuar, Herman Wahyudi, Yudhi Lastiasih & Dedi PrayitnoAnalysis of Embankment Slope Failure And Effectiveness Of Reinforcement With Full Displacement Column on Soft Soil (Case Study : Construction Of Padang Sicincin Toll Road Section STA 7+400 – 7+550) Firman Arifanto, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro & Sri Hastuti Hardiningsih Effectiveness And Stability Analysis Of Embankment Using Lightweight Embankment On Pasuruan - Probolinggo Toll Road Project Section 4, Indonesia Ruri Febri Ritwandanu, Herman Wahyudi, Yudhi Lastiasih & Hamim Mufijar Comparation of Limit Equilibrium Method (LEM) 2D on Safety Factor and Embankment Reinforcement Aisiyah Pramaisela Hapsari & Yudhi Lastiasih Volume 6, Special  Issue 2, January 2024 Determination of the Composition of Fly Ash, Bottom Ash and Lime or Cement Mixtures as Road Base Material. Case Study: Road Preservation of Sp. Kereng - Bereng Bengkel – Pilang – Pulang Pisau, Central Kalimantan Mochammad Yusuf Hilman, Noor Endah Mochtar & Soendiarto Excavation Slopes Stability Analysis with Cracked Soil in the Construction of the Serang – Panimbang Toll Road (STA 54+625) Under Maximum Rainfall Condition Wahyu Purnamayoga, Trihanyndio Rendy Satrya, Mahendra Andiek Maulana & Wahyu Supriyo Winurseto Correlation of Initial Soil Density and Maximum Soil Density Under Drying-Wetting Cycles and Their Soil Erodibility Tia Evriana, Trihanyndio Rendy Satrya, Mahendra Andiek Maulana & Wahyu Supriyo Winurseto The Improvement of Existing Slope Reinforcement System and The Design of Alternative Slope Reinforcements Case Study: Lainea-Awunio Road Section Km 98+050 South Konawe Regency, Southeast Sulawesi Province Nadia Kamila, Mohamad Khoiri & Freddy Siagian Slope Stability for Landslide in Road Preservation Working Packages Ende-Wolowaru and Junction-Kelimutu STA 8+425 Frans Andre Sasarari, Yudhi Lastiasih, Herman Wahyudi & Agustinus Junianto